Replication of Legionella Pneumophila in Human Cells: Why are We Susceptible? - Abu Khweek, Arwa; Amer, Amal (Frontiers in Microbiology, 2010)
Abstract Legionella is the causative agent of Legionnaires’ disease, a serious and often fatal form of pneumonia, in AIDS and immunocompromised patients. Humans are susceptible host for Legionella. This susceptibility arises from the ability of this intracellular pathogen to multiply in the alveolar macrophages and human monocytes. Legionella also replicates in several professional and non-professional phagocytic human-derived cell lines. With the exception of the A/J mouse strain, most mice strains are restrictive, thus they do not support Legionella replication. Therefore, A/J mice and their corresponding bone marrow-derived macrophages (BMDM) and alveolar macrophages have been used extensively to study Legionella replication. On the other hand, in the susceptible human hosts, Legionella utilizes several strategies to ensure intracellular replication and protect itself against the host immune system. Most of these strategies diverge toward preventing the fusion of the Legionella phagosome with the lysosome, inhibiting host cell apoptosis, activating survival pathways and sequestering essential nutrients for replication and pathogenesis. In this review, we summarize survival mechanisms employed by Legionella to maintain its replication in human cells. In addition, we highlight different human-derived cell lines that support the multiplication of this intracellular bacterium. Therefore, these in vitro models can be applicable and are reproducible when investigating Legionella/macrophage interactions at the molecular and cellular levels.